Legal Protection Of E-Commerce Consumers: A Review Of Regulation and Implementation - Moeslim, Yulia Jayaputri; Maryono, Maryono; Suasungnern, Sineerat (Journal Evidence Of Law, 2025)
This research aims to analyse the effectiveness of consumer legal protection regulations in e-commerce transactions in Indonesia, with a focus on the application of regulations in e-commerce platforms and the obstacles that hinder the optimisation of such protection. This research uses a normative juridical method and analyses various applicable laws and regulations, including the Consumer Protection Law, the Electronic Information and Transaction Law, as well as regulations related to personal data protection and e-commerce. The results show that although the existing regulations provide a strong legal basis, their implementation still faces challenges such as misalignment between regulations and the rapidly growing e-commerce practices, as well as limited supervision and law enforcement. Therefore, this study suggests the need for regulatory updates and increased supervision to create a consumer protection system that is more effective and adaptive to the development of the e-commerce sector.